Kajian Sediaan Orally Dissolving Film (ODF) - Muhammad Sultan Ramadhan; Uci Ary Lantika (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Oral route administration is the most common route and most widely known. However, this route is not always given beneficial. Some of the problems commonly encountered in this route are difficulty swallowing such hard tablets and capsules for patients who are at risk of choking on their use so the therapeutic effect is not optimal. Orally dissolving film (ODF) is a new invention that allows drugs to be used more comfortably than other oral solid preparations without the need for drinking water. In the oral cavity, there is vascularity that allows drugs to enter the systemic circulation without undergoing first-pass metabolism in the liver. ODF formulations consist of active pharmaceutical substances and excipients (film-forming polymers, plasticizers, saliva stimulants, sweeteners, flavoring agents). The ideal ODF preparation should be smooth, strong, and elastic but has a fast dissolving time. To ensure that ODF preparation is ideal, it is necessary to carry out evaluation tests including organoleptic, weight variety, film thickness, dissolution time, surface pH, folding endurance, tensile strength, percent elongation, drug content, transparency, and dissolution test. Abstrak. Rute pemberian oral merupakan rute paling umum dan paling banyak diketahui oleh masyarakat. Namun rute oral tidak selamanya memberikan keuntungan. Beberapa permasalahan yang umum ditemui pada rute ini yaitu kesulitan menelan seperti pada tablet dan kapsul keras bagi pasien yang berisiko tersedak pada penggunaanya sehingga efek terapi tidak optimal. Sediaan orally dissolving film (ODF) merupakan sebuah penemuan baru yang memungkinkan obat dapat digunakan secara nyaman dibandingkan sediaan solida oral lainnya tanpa memerlukan bantuan air minum. Dalam rongga mulut terdapat vaskularisasi yang membuat sebagian besar obat akan memasuki sirkulasi sistemik tanpa mengalami metabolisme lintas pertama di hati. Formulasi sediaan ODF terdiri atas zat aktif farmasi dan eksipien (polimer pembentuk film, plastisizer, penstimulasi saliva, pemanis, flavouring agent). Sediaan ODF yang ideal harus bersifat halus, kuat, elastis, namun memiliki waktu melarut cepat. Untuk memastikan sediaan ODF yang dihasilkan ideal perlu dilakukan uji evaluasi meliputi organoleptis, keragaman bobot, ketebalan film, waktu larut, pH sediaan, ketahanan lipat, kekuatan tarik, persen pemanjangan, penetapan kadar, transparansi, dan uji disolusi.